Expression Of Children's Character in Zafar Diyor's Poems - Chutboyeva Muxlisa Nuriddin qizi (Global Scientific Publishing, 2022)
In this article analyzes the image of children in the poetry of Zafar Diyar,this unique character and characteristics. The colorful spiritual world of children and the meaning of symbolic details are highlighted.
Keywords: Children’s literature; innocence; children’s poet; the cry of child